Aristotle on Legal Change - Poddighe, Elisabetta (Araucaria, 2019)
Aristotle’s discussion of legal change in Politics II.8 is the subject of this article. The aim is to show that Aristotle viewed legal change positively, when changes to the law are required, and that his discussion was mainly concerned with the two rather distinct roles of the demos and of the legislator. The analysis involves a re-examination of 1268b 25ss in book II of Aristotle’s Politics and its connection with book III. The analysis is also extended to Aristotle’s Rhetoric and Nicomachean Ethics, and to Plato’s Politicus and Laws.